GAMBARAN LAMA MASA PEMBERIAN ASI PADA BAYI UMUR 0-12 BULAN DI WILAYAH KERJA PUSKESMAS DANUREJAN IKOTA YOGYAKARTA - Sary Rosidawati; Reni Merta Kusuma (Universitas Respati Yogyakarta, 2018)
Background: Firstly, breast feeding supports to optimize the infant's growth. At the first 1000 days of newborn, the brain grows almost 75%. Infant in the age of 0-12 months become a crucial phase to determine their condition in their futures. The scope of breastfeeding in indonesia is 42% and year by year is getting decreased. According to data by Dinkes Kota Yogyakarta, they wrote, the scope of breastfeeding exclusively in Yogyakarta is the lowest of all, which is in the rate of 12, 31% in 2014. Research Objectives: Determining the scope of breastfeeding term for infant in the age of 0-12 months in Puskesmas Danurejan 1 Kota Yogyakarta Research Methods: This research is using descriptive quantitative methods. The amount of randomized sample is 52 samples who are consist of mother with infant in the age of 0-12 months in Puskesmas Danurejan 1 Kota Yogyakarta. The research is using cluster sampling technique where it is using questionnaire. The data analysis is used by univariate which will be described by the rates. Results: From 52 samples, 28 samples were found mostly mother with infant in the age of 0-12 months were giving breastfeeding ≥ 6 months or (52,8%). 21 samples (40,4%) were identified by the mother inthe age 20-35 years old with middle class educational background, 22 samples (42,3%) were identified by jobless mom, 15 samples (28,8%) were identified by disabilities moms. Conclusion: The length of breastfeeding in Puskesmas Danurejan 1 Kota Yogyakarta from 52 samples for infant in the age of ≥ 6months are 28 samples (52,8%) Keywords: the length of breastfeeding, for infant in the age of 0-12 months.